Coffee intake during pregnancy and childhood acute leukemia – A cohort study. (August 2020) - Madsen, Carina Nkoyo; Henriksen, Tine Brink; Ramlau-Hansen, Cecilia Høst; Parner, Erik Thorlund; Olsen, Jørn; Bech, Bodil Hammer
Highlights: Cohort study including more than 140, 000 mother/offspring dyads. This study does not support an association between moderate coffee intake during pregnancy and risk of acute leukemia in offspring. This study does not support an association between moderate coffee intake during pregnancy and risk of acute lymphoblastic leukemia. Abstract: Objectives: To estimate a possible association between coffee intake during pregnancy and risk of childhood acute leukemia by using a cohort design. Methods: We included data from two birth cohorts; the Danish National Birth Cohort and the Aarhus Birth Cohort. Recruitment of 141, 216 eligible pregnancies occurred from 1 August 1989 to 31 December 2012. Information on maternal prenatal coffee intake and covariates was collected in early second trimester of pregnancy. Information on childhood AL diagnosed in offspring was obtained from the Danish National Patient Register. We used competing risk time-to-event regression analysis, using the pseudo-observation method to estimate risk ratio (RR) with no coffee intake during pregnancy considered the reference group. Results: In total 96 children were diagnosed with AL, hereof 73 with acute lymphoblastic leukemia (ALL). Coffee intake of 0.5–3 cups/day during pregnancy was not associated with a higher risk of childhood AL; aRR = 0.89, 95 % confidence interval (CI): 0.48, 1.65, however, an intake of >3 cups/day resulted in aRR = 1.37, 95 % CI: 0.56, 3.32. Only including ALL as outcome we found similar results; aRR = 0.80, 95 % CI: 0.37–1.74 and aRR = 1.46 95 % CI: 0.52–4.09, respectively. Conclusion: We found no significant association between maternal coffee intake and risk of childhood AL but the number of cases was limited. The confidence limits does not exclude that a high prenatal coffee intake may increase the risk of childhood AL and larger studies based on prospective data are needed.